En defensa de la persona humana: la fundamentación de los derechos humanos a partir de la antropología del humanismo cívico (2005)
In the last years, human rights havebeen a very current subject, however, the attacks, against human person,increase every day. It is the reason why, is very important to knowthe real man ́s nature and which are the real human rights. It explains why we assume the anthropology of civic humanism(in Alejandro Llano’s version) as the fundamental point of viewin this article.